DESKRIPSI SIKAP PESERTA DIDIK TERHADAP TEXT BASED ANALOGY DAN CONCEPTUAL CHANGE TEXT SEBAGAI MEDIA PENGUBAHAN KONSEPSI PADA MATERI RANGKAIAN LISTRIK - Reza Hesti, M.Pd.; Johar Maknun; Selly Feranie (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
The research objective was to determine students' attitudes towards the use of CCT and TBA in changing the conceptions of electrical circuits. This type of research is a qualitative research that uses non-test instruments with a Likert scale of two response categories, namely strongly agree (S) and disagree (TS). The sample was selected purposively, namely 48 students who had studied the electrical circuit material and were detected in a state of misconception about the Electrical Circuit material. The results of the student's attitude response were obtained, then the approval was determined by the level of the category. Based on the results of the analysis, it was found that in general students gave positive responses regarding the role of TBA as a learning tool that could provide understanding so that they could change their wrong conceptions (misconceptions) into scientific conceptions when compared to CCT. This can be seen with 95.3% of respondents who gave positive attitudes for TBA and only 62% of respondents who gave positive attitudes for CCT, so that the category was very positive for TBA and positive for CCT in changing students' conceptions.